An extensive cervical vagal nerve schwannoma: A case report - Chai, Chiun Kian; Tang, Ing Ping; Prepageran, Narayanan; Jayalakshmi, Pailoor (Malaysian Medical Association, 2012)
Vagal nerve schwannoma is extremely rare. The majority of cases present with a slow growing neck swelling without neurological deficit. Magnetic resonance imaging is the gold standard investigation to establish a pre-operative diagnosis. We report a case of a 32-year-old man with an extensive right vagal nerve schwannoma involving the right jugular foramen and parapharyngeal space. The tumour was resected via a transcervical approach. Complete excision of the tumour is the key to prevent recurrence.